First record of Siphoninus phillyreae on pomegranate in Greece - Tsagkarakis, Antonios E. (ENTOMOLOGIA HELLENICA, 2012)
On June 2012, the ash whitefly Siphoninus phillyreae (Haliday) (Hemiptera: Aleyrodidae) was recorded for the first time on pomegranate in Greece. Its occurrence was observed in a pomegranate orchard at Kato Tithorea, in Fthiotida. Information on its morphology, biology and distribution is presented.